Analisis Faktor Yang Dapat Mempengaruhi Cash Holding Pada Perusahaan Manufaktur Di BEI - Angela Octavia, Merry Susanti (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study is to empirically examine the effect of market to book ratio, net working capital, financial leverage, profitability, capital expenditure, and size towards cash holding on manufacturing companies listed in Indonesia Stock Exchange from period 2016 – 2018. This study used 70 data from manufacturing companies that have been selected using purposive sampling method with total 210 data for three years. The data used are secondary data in the form of financial statements. This research used econometric views (E-Views) version 10 software to process the data. The result of research shows that profitability has a positive significant effect, and net working capital, capital expenditure, and size has a negative significant effect towards cash holding, while market to book ratio and financial leverage have no effect towards cash holding.